Heroes in The Resistance to Nature and Environment Destruction In Ã¢â‚¬Å“DhemitÃ¢â‚¬Â by Heru Kesawa Murti - Waluyo, Budi; Fitriana, Tya Resta; Veronika, Prima (Seloka: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2021)
The drama entitled Dhemit tells us about the construction of a cluster housing in a particular area in which the environment is sacrificed. Developing an area becomes an excuse that the environment which should be protected are destructed. The notion of environment is mutual. For those who preserve it will get the good but for those who destruct it will get the harm. In order to keep the balance, there should be people who take a good care of the environment. They should struggle with environmental crime. Resistance is another term for the struggle. Environmental crime is something that people should fight for. This should be done as the sustainability and balance are fundamental for the people’s better life. Destructing the environment is essentially the same as destructing the future itself because the people’s life strongly depends on the environment. In this study, qualitative information was described thoroughly and analytically. The description covers the environmental destruction occurred in the playscript of Dhemit by Heru Kesawa Murti as well as the form of resistance towards the environmental destruction. The approach used in this research was descriptive qualitative. This approach was used to interpret the deep meaning of a literary work on its relation the society. This interpretation was based on the notion that literary work is the resemblance of the real world. The author himself is a part of society who consciously or unconsciously is affected by the society.